Factors Related To Treatment Coverage Of Lung Tuberculosis In Timor Island - Batubara, Sakti Oktaria; Tahu, Sebastianus Kurniadi; Erna Febriyanti; Dimog, Eva Belingon Felipe (Jurnal Keperawatan Muhammadiyah, 2025)
Background: Treatment coverage (TC) of Tuberculosis (TB) as indicator of Tuberculosis is the main cause of death from infectious agents throughout the world. WHO has set 2030 as the end of TB, but treatment coverage in several countries is still low. Of all provinces in Indonesia, East Nusa Tenggara is the third lowest province with 40.1% coverage. On the Timor mainland, there are 3 districts with treatment coverage achievements below the national indicator (90%), namely South Central Timor District (43%), North Central East District (46%), and Belu District (71%). This condition will have an impact on achieving end TB by 2030. Several factors that may be the cause of the low contribution of treatment coverage include poverty, the ratio of community health centers/auxiliary health centers/pustu to sub-districts/population, motivation of TB program managers, availability of health insurance, cross-sectoral collaboration and TB management at the border. Objective: This research aims to determine the factors that contribute to the low achievement of treatment coverage. Method: the research used was quantitative study with cross sectional design. Result: the average age of respondents was 38,83 years (SD = 5,84), the average length of work of respondents was 10,87 (SD = 7.55). More than half, namely 66,3%, had a Diploma Nursing education. More of the three quarters of respondents, 75,9% were married. Nearly all patients were civil servants/P3K (94%). Most of the TB patients were from poor families (68,7%); all managers did not feel that there was cross-sectoral collaboration (94,0%). Only motivation that had significant relationship with TC.